IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN PESERTA PERTUKARAN PELAJAR DI SMAN 1 PADANG PANJANG DENGAN METODE AHP - Fadhilah, Habibatul; Yuspita, Yulifda Elin; Annas, Firdaus; Darmawati, Gusnita (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
The purpose of this study is to implement a Decision Support System (DSS) based on the Analytical Hierarchy Process (AHP) method to support the selection process of student exchange program participants in an objective and measurable manner. The background of this research is based on problems in the selection process, which are still subjective and lack transparency, causing confusion and dissatisfaction among students and parents. The system is designed to structure the hierarchy of criteria and alternatives, as well as calculate the priority weight of each student using the AHP method. Data processing was carried out through two approaches, namely manual calculation and the use of the Super Decisions application to compare the consistency of the results. The findings show that both approaches produced identical weights and rankings. Therefore, the AHP-based DSS is considered capable of providing accurate and efficient results, and is feasible to be implemented as a solution to improve objectivity, transparency, and efficiency in the selection process of student exchange program participants in the school environment.